Theory of human rights and democracy according to John Rawls, Jürgen Habermas and Fabien Eboussi Boulaga : A contribution to reconstructing the rule of law in Africa - (:unkn) unknown (My University, 2008)
This thesis would like to become a prospective, critical and comparative reading of Rawls, Habermas and Eboussi Boulaga?s theories of democracy, rule of law and human rights, through some of their basic Books. The aim is, through the Operative Concept of An inviolability of Human Dignity, to understand Rawls, Habermas and Eboussi Boulaga?s meaning of human rights, democracy and rule of law. This understanding is rooted on this question: how far this meaning could be universally and normatively valid? Is it meaningful within the contemporary debate on human rights? philosophy and on the reconstruction of the rule of law in Sub-Saharan African Countries? The answers to these questions are spreading out some logical arguments, which could determine these philosopher?s Route and their philosophical influences: they reached to the reconstruction?s theories of human rights, democracy and rule of law through a dynamic understanding of Rawls?s concept of political justice; of Habermas?s principle of discussion and communicational power of the rights? bearers, enjoying their private and public autonomy within the framework of deliberative democracy, and, finally, of Eboussi Boulaga?s critical evaluation, by the Muntu, of the organizational functionality of social connection through some anthropological categories. In this thesis, the category of possibility is understood, as a paradigm, i.e as ?bridge principle? or ?procedural principle?, which can permit not only to determine some juridical, political and philosophical insights of these philosophers? theories but also to outline some basic principles of a ?communal and federalist democracy?. These principles should appear as a pathway to reconstructing the rule of law in Sub-Saharan African Countries in general and in Cameroon particularly.
Keywords: African Research